Frictional performance evaluation of sliding surfaces lubricated by zinc-oxide nano-additives - Elagouz, Ahmed; Ali, Mohamed Kamal Ahmed; Xianjun, Hou; Abdelkareem, Mohamed A. A.; Hassan, Mohamed A. (Surface engineering, 2020)
Automobile engines consume more than 30% of fuel energy as frictional power waste. Therefore, this paper investigated the tribological properties of ZnO nanoparticles (NPs) as a nano-additive to improve the wear and friction trends of the piston ring/cylinder liner interface, especially in boundary lubrication. This improvement occurs due to the formation of a solid tribofilm layer on the sliding surfaces that acts as an indirect coating to help separate and protect the worn pairs. Tribological experiments were carried out under different speeds and loading circumstances using a ring-on-liner reciprocating test bench. The surface morphologies of the tested samples were analysed using EPMA, FE-SEM, a 3D surface profilometer and XPS to illustrate the key mechanisms of the ZnO nano-additives. The tribotest results show that the coefficient of friction and specific wear rate of the ring were reduced by 20-23% and 43-88%, respectively, using the ZnO nano-additives compared with the reference oil.